Preeclampsia and its relationship to pathological brain aging - Testo, Abigail A.; McBride, Carole; Bernstein, Ira M.; Dumas, Julie A. (Frontiers in Physiology, 2022)
Rationale: The development of preeclampsia during pregnancy may have long-term effects on brain aging in women. Associations between preeclampsia and vascular dementia have been established, however the connection between preeclampsia and Alzheimer’s disease has not been as thoroughly explored. Both preeclampsia and Alzheimer’s disease have been associated with misfolded amyloid beta proteins and inflammation; due to these similarities we examined the extent to which preeclampsia is related to brain aging. Objectives: This review used the PICO (Population, Intervention, Comparison, Outcome) format examining how a history of preeclampsia is linked to brain aging and the development of dementia. Data Sources: PubMed articles retrieved from 1990-2022. Data Extraction: PubMed was searched for studies of human participants conducted after 1990, published in English, and using the search terms preeclampsia and dementia. A total of 57 studies were found. Of those 57 studies 18 were review papers or systematic reviews and another 17 did not have preeclampsia or dementia as the focus or the primary focus of the paper was not maternal health; therefore 22 remained for inclusion in this review. PubMed was then searched for studies of human participants conducted after 1990, published in English, and using the search terms preeclampsia and brain aging. A total of 11 studies were found and of those 11 studies, four were systematic reviews and another five had an unrelated focus; therefore two remained for inclusion in this review. When the results of both searches were combined, there were a total of 24 papers to be reviewed. Synthesis: The studies we identified were used to investigate potential links between a history of preeclampsia and the development of dementia, as well as what might distinguish normal brain aging from cases of dementia. We then discussed findings related to potential underlying mechanisms of any such links. Lastly, we discussed possible interventions to improve long-term health outcomes following preeclampsia diagnosis as well as their implications. Conclusions: A history of preeclampsia is related to pathological brain aging and is likely an important risk factor for the development of Alzheimer’s disease in women later in life.